Alfred Pellan life & work - Lehmann, Maria Rosa (Art Canada Institute = Institut de l'art canadien, 2023)
"For fourteen years in the early twentieth century, Alfred Pellan (1906-1988) acted as a conduit between Canadian and European art. In 1926, at age twenty, he left Quebec for Paris, where he absorbed all that the city's avant-garde had to offer: he met Joan Miró, Pablo Picasso, and Fernand Léger, and he viewed a 1938 Surrealist exhibition that was a "transcendent" experience. Over the next several decades, Pellan divided his time between Paris and Montreal, making a distinctive-though often controversial-impact on modernism in Canada. In Alfred Pellan: Life & Work, author Maria Rosa Lehmann chronicles the storied artist's career from 1923 when the National Gallery of Canada purchased its first canvas by the then seventeen-year-old. The book examines his formative encounters in Paris and how people responded to his art at home. This landmark new publication addresses Pellan's formative years as well as his later career and how in 1952 he was chosen to show at the first Canadian pavilion at the Venice Biennale art fair-yet at the same time, he struggled for acceptance as he challenged the conservative art establishment in his home province. Brilliantly innovative and unwavering in his battle for artistic freedom, Pellan forged an independent vision that led him to being described by revolutionary art historian Guy Robert as the man who 'set Canadian painting free.'"--Publisher
Keywords: Pellan, Alfred / 1906-1988; Pellan, Alfred / 1906-1988 / Criticism and interpretation; Painters / Québec (Province) / Biography; Peintres / Québec (Province) / Biographies; Painters; Québec; Biographies; Criticism, interpretation, etc; Biografie